Entrepreneurship-Related Factors And Firm Performance: A Study On The Bumiputera Housing Developers In Peninsular Malaysia - Ali, Roslinda (2011)
Housing is a basic need for humans since they require roofs over their heads no matter where they reside. Apart from providing shelter and as a sense of security for a family to live in, housing also acts as a basis for investments for buyers who buy houses not for dwelling purposes, and as a creation of job employment opportunities in the upstream and downstream industries. The housing industry in Malaysia is dominated by the private sector, wherein they have exceeded the targets set for housing construction in the last three Malaysia Plan outlines consecutively, i.e. the Sixth, Seventh and Eighth Malaysia Plans.